Central Bank Digital Currency (CBDC) or stablecoins, or both – A central banking perspective - Terták, Elemér (Public Finance Quarterly, 2025)
With the above title, the Monetary Policy Section of the Hungarian Economic Association (MKT) organised an English-language webinar on Wednesday, November 5, 2025. Panellists included fellow workers from the Bank for International Settlements (BIS), Decent Investments, Hold Asset Management, and the National Bank of Hungary. The audience had the opportunity to intervene. The event was organised under the “Chatham House Rule”.1 This article provides an overview of the issues discussed at the session, as interpreted by the author. It therefore does not necessarily reflect the views of individual speakers, their institutions, or the industry as a whole.